Mechanics of Lower Limb Injuries in Basketball Players - Muñoz Andradas, Guillermo (KRONOS, 2022)
In this systematic review, studies from the last 10 years have been analyzed with the objective of evaluating the most common injuries in the lower extremities and the associated risk factors in the practice of basketball according to biomechanical factors. These injuries especially affect both men and women in preseason and postseason, although the incidence is higher in them. This may be due to a higher valgus compared to men, which means less stability. As for the most frequent injuries, those of the ankle stand out, where jumping is the mechanism that most affects, and that of the knee, which is influenced by flexion and internal rotation of the knee, as well as stability on landing. In the knee, the most frequent injury is that of the anterior cruciate ligament (ACL), with a higher incidence in women. It is usually given when making a stop, change of direction or landing. Similarly, slight knee flexion with tibial internal rotation and knee abduction destabilizes the joint and increases the risk of ACL injury. Other factors would be extreme external rotation of the foot and a lateral elevation of the hip.